2017
DOI: 10.1209/0295-5075/119/66007
|View full text |Cite
|
Sign up to set email alerts
|

Hydrodynamic front-like swarming of phoretically active dimeric colloids

Abstract: Self-propelled phoretic colloids have recently emerged as a promising avenue for the design of artificial swimmers. These swimmers combine purely phoretic interactions with intricate hydrodynamics which critically depend on the swimmer shape. Thermophobic dimer shaped colloids are here investigated by means of hydrodynamic simulations, from the single particle motion to their collective behavior. The combination of phoretic repulsion with hydrodynamic lateral attraction favors the formation of planar moving cl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(41 citation statements)
references
References 59 publications
0
41
0
Order By: Relevance
“…Here, the absorption differences between the two Janus hemispheres trigger a thermophoretic mobility in the thin interfacial layer and subsequently particle motion. Despite several groups working on this type of swimmer [62,63], to this moment, only few active-active interaction studies have been reported, showing that at decreased inter-particle distances, the motion is dominated by inter-particle interactions, and clusters form. We are not aware of any published consideration of passive particles [64], but interactions that confirm the observations in other motion mechanisms can be expected [65].…”
Section: Thermophoresismentioning
confidence: 99%
“…Here, the absorption differences between the two Janus hemispheres trigger a thermophoretic mobility in the thin interfacial layer and subsequently particle motion. Despite several groups working on this type of swimmer [62,63], to this moment, only few active-active interaction studies have been reported, showing that at decreased inter-particle distances, the motion is dominated by inter-particle interactions, and clusters form. We are not aware of any published consideration of passive particles [64], but interactions that confirm the observations in other motion mechanisms can be expected [65].…”
Section: Thermophoresismentioning
confidence: 99%
“…For phoretic SPPs, decreased propulsion at high densities due to a leveling of phoretic gradients has been observed in simulations [28][29][30]. Phoretic propulsion mechanisms occur for particles in externally imposed gradients of solute concentration, electric potential, or temperature [31,32]. When phoretic SPPs are close to each other, the gradients around the particles, and thus also the particle propulsion, decreases [31,[33][34][35].…”
Section: Introductionmentioning
confidence: 89%
“…Colloid shape has shown to importantly affect the phoretic particle properties [58][59][60], and also the induced flow field. Therefore, in the case of active phoretic dimers, the direction, shape, and intensity of the induced solvent velocity are determined by the surface properties of the swimmers and by their overall geometry [7,28,61]. Flow fields and stream lines around various thermophoretic dimers are shown in Fig.…”
Section: Single Dimeric Propertiesmentioning
confidence: 99%
“…Chemically active Janus colloidal particles have already shown clustering and self-assembled structures [22][23][24] as well as schooling behavior, and the formation of living crystals has already been observed for light-powered micromotors [25][26][27]. Interestingly, simulations of thermophobic dimers have recently shown the existence of a dynamic swarming behavior with front-like propulsion which occurs due to the specific combination of axial propulsion, phoretic repulsion, and hydrodynamic interactions [28]. There already exist various methods to perform simulations of active matter which account for the effects of propulsion, thermal fluctuations, hydrodynamics, and phoretic interactions [29][30][31][32][33].…”
Section: Introductionmentioning
confidence: 99%